Silvics and wood properties of the common timber tree species on Kolombangara - Burslem, D; Whitmore, T (Oxford Forestry Institute, University of Oxford, 1996)
Natural forest management in the Solomon Islands is at an important stage of development. Undisturbed forest below the altitudinal limit for logging has mostly been logged at least once, and the remaining unlogged area is under concession. It is therefore inevitable that the focus of forest management will shift from exploitation of pristine forest to management of the large area of logged forest over the next few years. However, the research on which management prescriptions for Solomon Islands forests would be based has only just started, and there is an urgent need for the kind of information required to design appropriate management systems. This Manual collates the published and unpublished information currently available on the silvicultural behaviour and wood properties of the 12 most common timber tree species in Solomon Islands natural forests. Most of the silvics information has been obtained from a recent analysis of data obtained during monitoring of populations of all trees of these species >4.9cm diameter on permanent sample plots on Kolombangara, as part of the Kolombangara Ecological Survey (KES). The KES has been a research project of the Solomon Islands Forest Department since 1964 and the plots have been monitored 15 times over the 30 year interval. The total area of permanent sample plots was 13.9ha in the early phases of the project but has declined over time as plots have been lost to cyclone damage and logging, although nine plots (5.7ha) have been monitored over the full 30 years of the study. The silvics data presented include accounts of species distribution and the ecology and demography of seedlings drawn from previous phases of the KES. The Manual also presents updates of tree growth and mortality rates under natural forest conditions, new data on changes in median and maximum crown exposure with tree size, and population responses to cyclones. Sections on plantation experience and wood properties are included, drawn from other published sources. Thus this Manual brings together in one place a summary of the accumulated knowledge on the twelve species described, which are the main timber-producing species of the Western Solomons. It is hoped that a single reference source will be of value for planning natural forest management. Fuller details on methodology and analysis are not given here but can be found in the source documents on which this Manual is based.